Animal models of chronic obstructive pulmonary disease. (June 2014) - Fricker, Michael; Deane, Andrew; Hansbro, Philip M
<x xml:space="preserve">Abstract</x> Introduction: Chronic obstructive pulmonary disease (COPD) is a leading global cause of mortality and chronic morbidity. Inhalation of cigarette smoke is the principal risk factor for development of this disease. COPD is a progressive disease that is typically characterised by chronic pulmonary inflammation, mucus hypersecretion, airway remodelling and emphysema that collectively reduce lung function. There are currently no therapies that effectively halt or reverse disease progression. It is hoped that the development of animal models that develop the hallmark features of COPD, in a short time frame, will aid in the identifying and testing of new therapeutic approaches. Areas covered: The authors review the recent developments in mouse models of chronic cigarette smoke-induced COPD as well as the principal findings. Furthermore, the authors discuss the use of mouse models to understand the pathogenesis and the contribution of infectious exacerbations. They also discuss the investigations of the systemic co-morbidities of COPD (pulmonary hypertension, cachexia and osteoporosis). Expert opinion: Recent advances in the field mark a point where animal models recapitulate the pathologies of COPD patients in a short time frame. They also reveal novel insights into the pathogenesis and potential treatment of this debilitating disease.